Anode-supported SOFCs based on Sm0.2Ce0.8O2−δ electrolyte thin-films fabricated by co-pressing using microwave combustion synthesized powders. Issue 3 (15th February 2016) - Sun, Haibin; Zhang, Yujun; Gong, Hongyu; Li, Qisong; Bu, Yunfei; Li, Teng
Abstract: Decreasing the electrolyte thickness is an effective approach to improve solid oxide fuel cells (SOFCs) performance for intermediate-temperature applications. Sm0.2 Ce0.8 O2− δ (SDC) powders with low apparent density of 32±0.3 mg cm −3 are synthesized by microwave combustion method, and SDC electrolyte films as thin as 10 μm are fabricated by co-pressing the powders onto a porous NiO–SDC anode substrate. Dense SDC electrolyte thin films with grain size of 300–800 nm are achieved at a low co-firing temperature of 1200 °C. Single cells based on SDC thin films show peak power densities of 0.86 W cm −2 at 650 °C using 3 vol% humidified H2 as fuel and ambient air as oxidant. Both the thin thickness of electrolyte films and ultra-fine grained anode structure make contributions to the improved cell performance.